Analisis Efisiensi Kinerja Lembaga Amil Zakat Di Indonesia - Ayief Fathurrahman; Ibnu Hajar (Universitas Islam Lamongan, 2019)
In the span of 74 years of Indonesia's independence, poverty, unemployment and social inequality remain major problems in national development. The Central Statistics Agency (BPS) recorded that as of March 2018, the number of poor people in Indonesia reached 25.95 million people or 9.82 percent of the total population of Indonesia. Seeing the problems that are so complex, it should be to pay attention to one solution in Islam to be able to prosper the community. Islam as rahmatan li al-‘a>lami>n has a solution through zakat, infaq and alms (ZIS) instruments. Zakat is one of the pillars of Islam consisting of shaha>dah, prayer, zakat, fasting and pilgrimage for those who are able. This study aims to analyze the level of efficiency of zakat management institutions in Indonesia in the period 2012-2016. The subjects in this study were the national zakat management organization with a purposive sampling technique. Of the 19 OPZs listed in the Ministry of Finance, two OPZs are chosen, namely the Rumah Zakat and Dompet Dhuafa. Data collection techniques use documentation techniques. The object examined is the financial statements for the period 2012-2016. The method used is Data Envelopment Analysis (DEA) with the production approach, input-output orientation and CRS assumptions. The results of this study show relative efficiency. National zakat management organization namely Rumah Zakat with a production approach, input-output orientation and CRS assumptions have Efficiency with 100% annual score. In the production approach, input-output orientation and the assumption of CRS Dompet Dhuafa have been Efficient in the first 3 years, namely in 2012, 2013 and 2014. However, in 2015 there was efficiency with an efficiency score of 78.71% and in 2016 it was 64.33%. Inefficiency occurs in the variable total assets, costs of socialization, collection and distribution of zakat.Keywords: data envelopment analysis, efficiency, production approach, zakat management agency